Prognostic utility of plasma lactate measured between 24 and 48 h after initiation of early goal-directed therapy in the management of sepsis, severe sepsis, and septic shock - Chertoff, Jason (J Intensive Care, 2016)
BACKGROUND: Based on the proven efficacy of lactate in predicting mortality and morbidity in sepsis when measured early in the resuscitative protocol, our group hypothesized that this utility extends later in the course of care. This study sought to investigate the prognostic potential of plasma lactate clearance measured 24–48 h after the initiation of treatment for nonsurgical patients with sepsis, severe sepsis, and septic shock. METHODS: Plasma lactate values, measured 24–48 h after the initiation of treatment, were collected in nonsurgical septic, severe septic, and septic shock patients. The primary outcome was 30-day mortality, while secondary outcomes included requirements for vasopressors and boluses of intravenous fluids. Analysis of these three outcomes was performed while controlling for clinical severity as measured by Sequential Organ Failure Assessment (SOFA), renal dysfunction, and hepatic dysfunction. Lactate clearance was defined as the percent change in plasma lactate levels measured after 24–48 h of treatment from the plasma lactate level at initial presentation. RESULTS: Two hundred twenty-nine nonsurgical patients were divided into two groups, clearers (above median lactate clearance [31.6 %]) and nonclearers (below median lactate clearance [31.6 %]). The adjusted odds ratio of mortality in clearers compared to nonclearers was 0.39 (CI 0.20–0.76) (p = 0.006). For vasopressor requirement, the adjusted odds ratio was 0.41 (CI 0.21–0.79) in clearers compared to nonclearers (p = 0.008). For intravenous fluid bolus requirement, the adjusted odds ratio was 0.81 (CI 0.48–1.39) in clearers compared to nonclearers (p = 0.45). CONCLUSIONS: Lower plasma lactate clearance 24–48 h after the initiation of treatment is associated with higher 30-day mortality and requirements for vasopressors in nonsurgical septic patients and may be a useful noninvasive measurement for guiding late-sepsis treatment. Further investigation looking at mechanisms and therapeutic targets to improve lactate clearance in late sepsis may improve patient mortality and outcomes.